Bis[N-(8-quinolyl)pyridine-2-carboxamidato-κ(3) N,N′,N′′]manganese(III) perchlorate monohydrate - Meng, Qingguo (International Union of Crystallography, 2008)
The Mn(III) ion in the title complex, [Mn(C(15)H(10)N(3)O)(2)]ClO(4)·H(2)O, is coordinated meridionally by six N atoms from two tridentate N-(8-quinolyl)pyridine-2-carboxamidate ligands, yielding a distorted octahedral coordination geometry. The two ligands are nearly planar and their mean planes are almost perpendicular, with a dihedral angle of 86.7 (2)°.